Healthy lifestyle behaviors in sophomore nursing students: A descriptive correlational study - Chunta, Kristy S. (Building Healthy Academic Communities Journal, 2020)
Aim: The purpose of this research was to describe health perceptions, behaviors, and perceived stress of undergraduate nursing students and to determine if supportive incentives improved students’ healthy lifestyle behaviors. Background: Nurses have a primary responsibility in promoting health in the United States. Nursing students will become the future health workforce and must understand the importance of personal health and wellness, even before entering the profession. Methods: This descriptive study used a convenience sample of sophomore nursing students (N = 65) from one state university in the Northeast. Students’ motivators and barriers of a healthy lifestyle, perceived difficulty in maintaining a healthy lifestyle, perceived stress, and personal health rating were measured at the beginning and end of the semester. Results: Small and moderate correlations were noted among several variables. Paired t-tests revealed statistically significant findings for students’ perceived difficulty in maintaining a healthy lifestyle, health barriers, and personal health rating. Open-ended responses identified time and money/cost as the greatest barriers to making healthy lifestyle decisions. Supportive incentives offered throughout the semester did not increase participation in wellness activities. Conclusions: Undergraduate nursing students reported barriers and difficulties in relation to maintaining healthy lifestyle behaviors. Future research should focus on the challenges that college students face and provide interventions to promote health and wellness behaviors. Continued research with nursing students may identify healthy lifestyle challenges that are unique to this group of students.